Respostas
respondido por:
2
x + y = 15
x = 15 - y
x . y = 14
(15 - y) y = 14
15 y - y² = 14
-y² + 15 y - 14 = 0
Δ = b² - 4 a. .c
Δ = 15² = - 4 . -1 . - 14
Δ = 225 - 56
Δ = 169
\/¨¨169 = 13
x = - b +ou- 13/2.-1
x´= -15 + 13/-2
x´= -2/-2
x´= 1
x" = -15 - 13 /-2
x" = -28/ -2
x" = 14
S = {1,14}
x = 15 - y
x . y = 14
(15 - y) y = 14
15 y - y² = 14
-y² + 15 y - 14 = 0
Δ = b² - 4 a. .c
Δ = 15² = - 4 . -1 . - 14
Δ = 225 - 56
Δ = 169
\/¨¨169 = 13
x = - b +ou- 13/2.-1
x´= -15 + 13/-2
x´= -2/-2
x´= 1
x" = -15 - 13 /-2
x" = -28/ -2
x" = 14
S = {1,14}
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás